Rituximab Treatment in a Patient With Primary Biliary Cirrhosis and Rheumatoid Arthritis - Betül SARGIN,; Gülcan GÜRER, (Archives of Rheumatology, 2016)
Primary biliary cirrhosis (PBC) is an autoimmune liver disease,(1) with symptoms including fatigue, cognitive impairment, and pruritus.(2) Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease characterized by joint destruction and disability.(3) Herein, we report a female patient with PBC and RA successfully treated with rituximab. A 72-year-old female patient who had been diagnosed with PBC for three years complaining of pain, swelling, and warmth in her wrists and ankles, with accompanying morning stiffness lasting for one hour for one year applied to our outpatient clinic. The diagnosis of PBC was considered upon two of three objective criteria: (i) biochemical evidence of cholestasis based on elevated level of serum alkaline phosphatase (1.5 times the upper limit of normal); (ii) presence of serum antimitochondrial antibodies (titers of 1:40); and (iii) liver histology characterized by nonsuppurative cholangitis and interlobular bile duct destruction.(4) She was taking ursodeoxycholic acid for PBC treatment. Tenderness and warmth were detected in both wrists and ankles in musculoskeletal system examination. Patient’s laboratory findings are presented in Table 1. X-rays of wrists and ankles were consistent with RA. Following RA diagnosis, treatment with oral sulfasalazine (2 g/day), hydroxychloroquine (400 mg/day), and prednisolone (10 mg/day) was initiated. After refractoriness to synthetic disease-modifying <t1> antirheumatic drugs (Disease Activity Score 28: 6.96) and tumor necrosis factor alpha inhibitor therapies (etanercept and adalimumab), patient received rituximab cycles with two infusions every six months. Response to treatment was assessed by Disease Activity Score 28. After the second cure, Disease Activity Score 28 decreased to 4.5, and serum alkaline phosphatase and gamma glutamyl transferase levels regressed to 82 U/L and 23 U/L, respectively. Her symptoms regressed. The prevalence of the association of PBC and RA is 1.8% to 5.6%.(5) B cells may have important role in the pathogenesis of these diseases. Tsuda et al.(6) and Jopson et al.(2) suggested rituximab as a successful treatment for PBC. In case reports by Lazrak et al.(1) and Polido-Pereira et al.,(7) patients had good clinical and laboratory responses with rituximab treatment for RA although abnormalities in liver tests were persistent after five months and one year, respectively. Although response to rituximab treatment have been reported differently in PBC and RA patients in the literature, our case suggests rituximab as a successful treatment option for these diseases supported with good responses in clinical and laboratory parameters. In conclusion, rituximab treatment is an effective treatment option for patients with PBC and RA.